A Bibliometric Analysis of Research on the Convergence of Artificial Intelligence and Blockchain in Smart Cities - Morteza Alaeddini; Maryam Hajizadeh; Paul Reaidy (Smart Cities, 2023)
Smart cities aim to enhance the quality of life for citizens by integrating information technology in various aspects of daily life. This paper focuses on recent innovations in the integration of two prominent technologies, artificial intelligence (AI) and blockchain, to manage complex interactions between smart connected devices, individuals, government agencies, and the private sector. By conducting a systematic scientometric analysis and visualization of 505 articles published between 2017 and 2023, we uncover the social, conceptual, and intellectual structures of the literature in this field through co-authorship, co-word, and co-citation networks. Our analysis identifies key insights, research hotspots, specialties, and emerging trends by examining important nodes in the bibliometric networks. The findings of this study can be of interest to both academics and practitioners working in the fields of AI, blockchain, and smart cities.